10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background The comparative effectiveness of different exercise modalities on systemic inflammation in patients with metabolic syndrome (MetS) remains poorly defined. Objective To systematically evaluate and rank the effects of aerobic exercise (AE), resistance training (RT), and combined training (COM) on inflammatory markers (CRP, TNF-α, and IL-6) in MetS. Methods A network meta-analysis of 28 randomized controlled trials (RCTs) was conducted. Data were synthesized using frequentist random-effects models. Treatment efficacy was ranked using the Surface Under the Cumulative Ranking Curve (SUCRA). Results Compared to the control group, all exercise modalities were associated with reductions in TNF-α levels, though the strength of this evidence is limited by high heterogeneity and potential publication bias. Among the interventions, COM showing the greatest effect (SMD = -1.74; 95% CI: -3.06 to -0.43; SUCRA = 75.7%), followed by RT and AE. For CRP, significant reductions were observed in COM (SMD = -0.79; 95% CI: -1.36 to -0.21; SUCRA = 86.8%) and AE (SMD = -0.64; 95% CI: -0.95 to -0.32), while RT demonstrated a smaller effect. No modalities reached statistical significance for IL-6, although RT ranked highest in SUCRA (75.8%). Notably, CRP findings were robust with moderate certainty and no publication bias (p = 0.86), whereas TNF-α and IL-6 exhibited significant publication bias (p < 0.05) and extreme heterogeneity (I2 > 90%). Conclusion Exercise, particularly COM, appears to be a promising intervention for reducing CRP and TNF-α in MetS. While the findings for CRP are robust, results for TNF-α should be interpreted with caution due to observed heterogeneity and potential publication bias.